Future of Colorectal Cancer Screening: From One-Size-FITs-All to Tailor-Made - Kortlever, Tim; van der Vlugt, Manon; Dekker, Evelien (Frontiers in Gastroenterology, 2022)
Screening for colorectal cancer (CRC) and its precursor lesions, advanced adenomas (AA), has been shown to effectively reduce CRC-related mortality. However, the method of CRC screening varies among countries. Primary colonoscopy screening is the most effective screening option from an individual point of view, but it is costly and population-wide participation rates are relatively low. Repeated screening with a fecal immunochemical test (FIT) is a non-invasive and inexpensive way to select individuals at high risk for CRC for colonoscopy. Despite its widespread use and mostly high participation rates, FIT is not perfect. Its sensitivity for advanced neoplasia (AN) is low. Besides, the false positivity rate of FIT is relatively high. This leads to unnecessary colonoscopies, anxiety, and risks among FIT-positives. New strategies need to be developed to improve CRC screening. In the past years, much research has been undertaken on risk-based screening or risk models. These include tests consisting of multiple risk factors and/or biomarkers that either assess the risk of disease at a single point in time (cross-sectional risk models) or predict the risk of developing CRC in the future (longitudinal risk models). We provide an overview of the developments on risk models for CRC screening and discuss some of the obstacles that need to be overcome to enable widespread implementation in existing CRC screening programs.